BEYOND THE GAME: INTERNATIONAL MEDIA ATTITUDES TOWARD INDONESIA'S CANCELLATION OF THE U20 WORLD CUP - Syahputra, Fikry Prastya; Ganie, Rohani; Ridlo, Muhammad Rasyid; Febrilliandika, Bayu (University of Kuningan, 2024)
In March 2023, Indonesia was confronted with a situation that was also a worldwide concern. The hosting of the U20 World Cup in Indonesia has been cancelled. This study, however, will not address the reasons why this could happen but rather the attitudes of the world's newspapers in reporting on the subject. It is significant because, as a nation which constantly seeking global recognition, Indonesia should be introspective by understanding the global community's perspectives on the problems that exist in Indonesia, which can be illustrated by news about Indonesia that exists in foreign newspapers. Furthermore, attitude analysis can be done using Appraisal Theory. This study sampled three articles from online news: BBC, CNA, and The Straits Times. The data were analyzed by adopting a mix-method. The results obtained that the three news articles had negative attitudes perspective. Furthermore, the findings of this study's analysis can be used as teaching material for language and communication students interested in becoming journalists or writing articles for print and online publications.